2021
DOI: 10.1093/plphys/kiab492
|View full text |Cite
|
Sign up to set email alerts
|

Inactivating transcription factorOsWRKY5enhances drought tolerance through abscisic acid signaling pathways

Abstract: During crop cultivation, water-deficit conditions retard growth, thus reducing crop productivity. Therefore, uncovering the mechanisms behind drought tolerance is a critical task for crop improvement. Here, we show that the rice (Oryza sativa) WRKY transcription factor OsWRKY5 negatively regulates drought tolerance. We determined that OsWRKY5 was mainly expressed in developing leaves at the seedling and heading stages, and that its expression was reduced by drought stress and by treatment with NaCl, mannitol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 69 publications
(90 reference statements)
0
44
0
Order By: Relevance
“…Plants survive in complex and variable environments and are often subjected to various biotic and abiotic stresses, and WRKY transcription factors have important roles in plant growth and development and in coping with adverse stresses ( Chen et al., 2020a ; Chen et al., 2020b ). For example, WRKY transcription factors affect lignin synthesis ( Miyamoto et al, 2020 ) and fruit ripening ( Gan et al, 2021 ) during plant growth and development; additionally, WRKY TFs are involved in plant responses to drought ( Lim et al, 2022 ), salt ( Fang et al, 2021 ), and low temperature ( Zhang et al, 2019a ) and a variety of other stress responses. It has been shown that WRKY transcription factors initiate a response in plants mainly by interacting with the cis-acting element W-box on the target gene promoter, which acts as a transcriptional activator or repressor of downstream gene expression ( Bakshi & Oelmüller, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plants survive in complex and variable environments and are often subjected to various biotic and abiotic stresses, and WRKY transcription factors have important roles in plant growth and development and in coping with adverse stresses ( Chen et al., 2020a ; Chen et al., 2020b ). For example, WRKY transcription factors affect lignin synthesis ( Miyamoto et al, 2020 ) and fruit ripening ( Gan et al, 2021 ) during plant growth and development; additionally, WRKY TFs are involved in plant responses to drought ( Lim et al, 2022 ), salt ( Fang et al, 2021 ), and low temperature ( Zhang et al, 2019a ) and a variety of other stress responses. It has been shown that WRKY transcription factors initiate a response in plants mainly by interacting with the cis-acting element W-box on the target gene promoter, which acts as a transcriptional activator or repressor of downstream gene expression ( Bakshi & Oelmüller, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Six OsWRKYs (OsWRKY5, OsWRKY11, OsWRKY30, OsWRKY45, OsWRKY47, and OsWRKY55) are known regulators of drought tolerance in rice [ 15 , 16 , 17 , 18 , 19 , 20 ]. To examine the relationships among these TFs, we constructed a phylogenetic tree.…”
Section: Resultsmentioning
confidence: 99%
“…Rice ( Oryza sativa L.), which is one of the most important monocot crops, has 103 WRKY TFs, including 28 Group III members [ 13 , 14 ]. Among rice WRKY TFs, OsWRKY5, OsWRKY45, and OsWRKY55 decrease drought tolerance, while OsWRKY11, OsWRKY30, and OsWRKY47 increase it [ 15 , 16 , 17 , 18 , 19 , 20 ]. OsWRKY45, OsWRKY47, and OsWRKY55 are WRKY Group III TFs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that OsWRKY108 was an integrative regulator of P homeostasis and leaf inclination (Wang et al, 2021 ). The inactivated OsWRKY5 enhanced drought tolerance through abscisic acid signaling pathways (Lim et al, 2021 ). At 4°C, overexpression of OsWRKY76 improved the tolerance to low-temperature stress (Babitha et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%